Financial system transformation and growth strategy: A case study of inartgrity's sustainable expansion preparation - Anchilia Alexandra; Taufik Faturohman (Priviet Social Sciences Journal, 2026)
INARTGRITY, an education center based in Kelapa Gading, Jakarta, Indonesia, is nearing full capacity and plans to expand by opening a second branch in the near future. This study evaluates company readiness, project feasibility, and strategic recommendations for long-term sustainability, supported by risk management, and an implementation plan. Readiness is assessed using the RBV, VRIO, and financial ratio analyses. The expansion is modelled under two alternatives: buying or renting a commercial house. The buy option requires an initial investment of IDR 5,185,000,000 with a 12,52% discount rate over a 10 years horizon, while the rent option requires IDR 985,000,000 with an 11,57% discount rate over 5 years. Discounted cash flow analysis is used to compute NPV, PBP, IRR, PI, and ANPV, complemented by sensitivity analysis and Monte Carlo simulation to identify key drivers and the probability distribution of the NPV. The buy option yields NPV IDR 3,571,624,197, IRR 21,34%, PI 1,36, PBP 7 years 10 months, and ANPV IDR 645,679,440. The rent option yields NPV IDR 1,743,809,195, IRR 44,75%, PI 2,77, PBP 3 years 2 months, and ANPV IDR 478,293,264. Although buying provides a higher ANPV, renting is recommended because it offers a much higher IRR and PI, faster payback, lower initial capital, and remains robust under sensitivity and simulation, with approximately 99% probability of a positive NPV.